Feasibility study relating to a telecommunication link between Guyana and Suriname (SOFRECOM VincennesFR)
Describes the network. Provides a background to the project, traffic analysis and traffic forecast. Highlights requirements and cost estimate of the project; and suggests training needs. An economical study is also supplied.
DC